2017
DOI: 10.2217/bmm-2016-0266
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of the C-Reactive Protein-To-Prealbumin Ratio in Medical ICU Patients

Abstract: CRP/PAB were independently correlated with hospital mortality and TLSH in medical intensive care unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 33 publications
1
30
1
Order By: Relevance
“…The current study revealed poor association between CRP/albumin ratio and PICU stay. Compared with our finding in pediatric patients, Li et al 28 have demonstrated significantly increased total length of hospital stay in adult patients admitted to medical ICU with CRP/prealbumin more than 0.24. Another study has reported a significantly higher CRP/prealbumin in ICU adult patients with severe pancreatitis who had a longer period of ICU stay.…”
Section: Discussioncontrasting
confidence: 99%
“…The current study revealed poor association between CRP/albumin ratio and PICU stay. Compared with our finding in pediatric patients, Li et al 28 have demonstrated significantly increased total length of hospital stay in adult patients admitted to medical ICU with CRP/prealbumin more than 0.24. Another study has reported a significantly higher CRP/prealbumin in ICU adult patients with severe pancreatitis who had a longer period of ICU stay.…”
Section: Discussioncontrasting
confidence: 99%
“…However, using of hs-CRP alone to predict MACE in patients with ACS may be limited. Inflammation can induce malnutrition, which may exert a negative effect on the management of inflammation 18 . PAB as a parameter in the evaluation of nourishment state was suppressed in an inflammatory environment 10 .…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the C-reactive protein/prealbumin ratio in medical intensive care unit patients has been associated with mortality [35], and a low C-reactive protein/prealbumin ratio in surgical patients predicted the successful closure of gastrointestinal fistulas [36]. Routine measurement of prealbumin has been advocated to be a useful nutritional and prognostic indicator in non-ICU patients without inflammation [34].…”
Section: Serum Visceral Proteins As Biomarkers Of the Nutritional mentioning
confidence: 99%